Kebijakan Dividen, Struktur Modal dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Manufaktur - Apolinaris S. Awotkay; Yumiad Fernando Richard (Musamus University, Merauke Papua Indonesia., 2020)
This study aims to determine the effect of dividend policy, capital structure and company size on profitability. This research was conducted in the manufacturing sector which is listed on the Indonesian stock exchange (BEI). This type of research is descriptive quantitative. The population in this study were all 163 companies listed on the Indonesia Stock Exchange in 2014-2018 using purposive sampling technique and taking a sample of 44 companies. The data analysis method used in this study used multiple linear regression processed with the SPSS program. Before linear regression is made, the model prerequisite test has been carried out using the classical or normality assumption test which consists of the normality test, linearity test, aoutocorrelation test, multicollinearity test and heteroscedasticity test. This study found that: 1. Dividend policy has no positive and significant effect on profitability. 2. Capital structure has a positive and insignificant effect on profitability. 3. Company size has a positive and insignificant effect on profitability and 4. Dividend policy, capital structure and firm size simultaneously have a significant effect on profitability (ROE). The results of this study are different from previous studies.